2002
DOI: 10.1093/humrep/17.4.990
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of DNA damage in human sperm assessed by single cell gel electrophoresis (Comet assay) and its relationship to fertilization and embryo development

Abstract: This study contributes to the evidence of DNA damage within sperm. High loads of DNA damage measured by the Comet assay were predictive of failure of embryo development after ICSI. As it is likely that sperm with DNA damage contributed to successful fertilization and in-vitro development, potential adverse effects remain to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
265
3
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(291 citation statements)
references
References 57 publications
13
265
3
10
Order By: Relevance
“…High levels of sperm DNA damage have been reported to affect fertility potential, increase the risk of recurrent miscarriages, decrease the chances of a successful implantation, and possibly lead to negative effects on the health of offspring [4,5]. Sperm DNA integrity as assessed by terminal desoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) [6], sperm chromatin structure assay (SCSA) [7,8], and Comet assay [9], were also shown to be compromised with advancing age. However, this notion was not supported by all studies [10][11][12], and the results varied according the technique used for the detection of DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of sperm DNA damage have been reported to affect fertility potential, increase the risk of recurrent miscarriages, decrease the chances of a successful implantation, and possibly lead to negative effects on the health of offspring [4,5]. Sperm DNA integrity as assessed by terminal desoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) [6], sperm chromatin structure assay (SCSA) [7,8], and Comet assay [9], were also shown to be compromised with advancing age. However, this notion was not supported by all studies [10][11][12], and the results varied according the technique used for the detection of DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed that DNA damage had a positive correlation to abnormal sperm morphology but a negative correlation to sperm count. Unexpectedly, a positive correlation between DNA damage and motility was shown in the study [12]. In a study performed using the alkaline COMET assay, NTcondensed and NT-decondensed methods, Irvine et al found a significant negative correlation between sperm DNA damage and semen quality, especially in sperm count.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, this observation is highly consistent with findings from studies analyzing sperm DNA fragmentation and IVF outcomes. The majority of those studies demonstrated high sperm DNA fragmentation does not preclude fertilization but negatively impacts subsequent embryo development and reduces pregnancy rates [12,13,[15][16][17]. The initial steps of embryonic development from fertilization up to the 6-8 cell cleavage stage occur essentially independent of the embryonic/ paternal genome and are predominately under the influence of maternal transcripts packaged into the oocytes at the time of ovulation [18].…”
Section: Discussionmentioning
confidence: 99%